Triple Therapy of Umeclidinium + Inhaled Corticosteroids/Long-Acting Beta2 Agonists for Patients with COPD: Pooled Results of Randomized Placebo-Controlled Trials. Issue 1 (June 2016) - Siler, Thomas; Kerwin, Edward; Tombs, Lee; Fahy, William; Naya, Ian
Abstract Introduction Data on triple therapy (long-acting muscarinic antagonist [LAMA] + inhaled corticosteroid/long-acting beta2 -agonist [ICS/LABA]) in symptomatic patients with chronic obstructive pulmonary disease (COPD) are limited. This post hoc analysis aimed to determine the efficacy of once-daily umeclidinium (UMEC; 62.5 μg) or placebo (PBO) plus open-label fixed-dose ICS/LABA in symptomatic patients with COPD. Methods Data were pooled from four randomized, double-blind, parallel-group trials (ClincalTrials.gov identifiers: NCT01772134, NCT01772147, NCT01957163, NCT02119286). Inclusion criteria included COPD diagnosis, modified Medical Research Council dyspnea scale score ≥2 and forced expiratory volume in 1 s (FEV1 ) <70% predicted. Following a 4-week run-in with once-daily or twice-daily ICS/LABA, patients were randomized to UMEC 62.5 μg or PBO as add-on therapy for 12 weeks. The efficacy of UMEC 62.5 μg + ICS/LABA or PBO + ICS/LABA in the intent-to-treat (ITT) population and subgroups with Global initiative for chronic Obstructive Lung Disease (GOLD) B and D COPD, and once-daily or twice-daily ICS/LABA was investigated. Outcomes included: trough FEV1, rescue-medication use, St George's Respiratory Questionnaire (SGRQ) score, moderate/severe exacerbations. Adverse events (AEs) were assessed. Results UMEC 62.5 μg + ICS/LABA (ITT:n  = 819) provided clinically important improvements in trough FEV1 versus PBO + ICS/LABA [ITT:n  = 818; 130 mL (95% CI 112, 147);P  < 0.001] at Day 85. Similar improvements occurred in all four subgroups (119–147 mL; allP  < 0.001). In the ITT population, UMEC 62.5 μg + ICS/LABA decreased rescue-medication use, improved SGRQ score, and reduced short-term exacerbation risk (allP  ≤ 0.004 versus PBO + ICS/LABA). These three outcomes also improved consistently with UMEC 62.5 μg + ICS/LABA versus PBO + ICS/LABA with both ICS/LABAs and in the GOLD D subgroup. In the GOLD B subgroup a statistically significant benefit was observed in lung function and proportion of SGRQ responders. AE incidences were similar with UMEC 62.5 μg + ICS/LABA versus PBO + ICS/LABA. Conclusion In symptomatic patients with COPD, triple therapy with UMEC 62.5 μg + ICS/LABA improved lung function, reduced rescue-medication use, improved health-status and reduced exacerbation risk versus PBO + ICS/LABA, with similar safety profiles. Funding GSK (study number 202067).